Evidence for TeV gamma ray emission from Cassiopeia A - Aharonian, Felix A.; Akhperjanian, A.; Barrio, J.; Bernlöhr, Konrad; Hermann, G.; Heusler, A.; Hofmann, Werner; Kohnle, A.; Konopelko, Alexander; Kornmeyer, H.; Kranich, D.; Krawczynski, Henric; et al. (Astronomy and astrophysics, 2001)
232 hours of data were accumulated from 1997 to 1999, using the HEGRA Stereoscopic Cherenkov Telescope System to observe the supernova remnant Cassiopeia A. TeV γ-ray emission was detected at the level, and a flux of above 1 TeV was derived. The spectral distribution is consistent with a power law with a differential spectral index of between 1 and 10 TeV. As this is the first report of the detection of a TeV γ-ray source on the "centi-Crab"scale, we present the analysis in some detail. Implications for the acceleration of cosmic rays depend on the details of the source modeling. We discuss some important aspects in this paper.